Seminar Bisnis Online Bersama UMKM Makanan dan Minuman Sukolilo - In’am Widiarma; Nenny Syahrenny; Tegowati Tegowati (Jurnal Pengabdian Masyarakat (ABDIRA), 2022)
The Covid-19 pandemic has affected almost all sectors and lines of life, including MSMEs, which are actually the driving force of the Indonesian economy. MSMEs have started to rise again with the knowledge and knowledge they have, but there is still one obstacle that occurs for Sukolilo MSMEs who are involved in the food and beverage sector, which is related to the delivery and distribution of goods, therefore we as academics are collaborating with Paxel Surabaya branch to help and solve the problems of the MSMEs. The method of this service activity is carried out with seminars consisting of training, knowledge of financial literacy in Indonesia and explaining the mechanism for delivering goods through digitalization or an integrated delivery system. After that, we provide assistance by installing applications on software on communication tools for MSME actors and the process of sending goods. Paxel's role can provide real solutions to the problems of MSMEs for food and beverage delivery that often occur so far.